Anion‐Binding Catalysis by Electron‐Deficient Pyridinium Cations1. Issue 43 (10th September 2014) - Berkessel, Albrecht; Das, Somnath; Pekel, Daniel; Neudörfl, Jörg‐M.
Abstract A new activation principle in organocatalysis is presented: halide binding through Coulombic interactions. This mode of catalysis was realized by using 3, 5‐di(carbomethoxy)pyridinium ions that carry an additional electron‐withdrawing substituent on the nitrogen atom, for example, pentafluorobenzyl or cyanomethyl. For the N‐pentafluorobenzyl derivative, Coulombic interaction with the pyridinium moiety is complemented in the solid state by anion–π interactions with the perfluorophenyl ring. Bromide and chloride are bound by these cations in a 1:1 stoichiometry. Catalysis of the CC coupling between 1‐chloroisochroman (and related electrophiles) with silyl ketene acetals occurs at −78 °C and at low catalyst loading (2 mol %).